(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Background - Sex determination from skeletal remains is vital. Considering regional variability, need for population specific data is often emphasized to identify sexually dimorphic potential of bony skull fragments. However, limited amount of data is available especially from Eastern Indian population. In this context, different metric assessment of mastoid region in human skull were considered based on discriminant function formula. Methods – A total of 40 male and 35 female adult human skulls were studied. Traditional measurements of four linear parameters of mastoid region on both sides were taken according to standard anthropometric references. The potential of mastoid region dimension in sex estimation was evaluated with ROC analysis and discriminant function formula. Results – All linear mastoid parameters yielded significant difference (p